THE INFLUENCE OF PRICE AND CONSUMER INCOME ON PRODUCT PURCHASING DECISIONS AT THE ANING SHO, MILANGODAA VILLAGE - Karlin Hulantu; Karlina Napu; Nuzmerini Rauf (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The aim of this study is to determine the influence of prince and consumer income on product purchasing decisions at the Aning Shop. This study uses a quantitative approach. The sampling technique in this research used a probability sanmpling technique where the number of samples obtained was 30 respondents.The date analysis technique used is multiple linear regression. The test results show that product prices have a positive and significant affect on product purchasing decicions at the Aning Shop.this is indicated by the caculated t of 2.880 which is greater than the t table value of 2.052. the consumer income variable has a positive and in significant effect on product purchasing decisions at the Aning Shop. This indicated by the calcuted t value of 1.757 which is smaller than the t table value of 2.052